Influencia de los hábitos alimenticios en el rendimiento escolar en los alumnos de quinto y sexto de básica de la Escuela "Yaguachi" del Recinto Poco a Poco, Cantón Jujan, Provincia del Guayas periodo octubre 2019- marzo 2020. - Santa Cruz Martínez, Daysi Elizabeth (2020)
The research done to the students of Fifth and Sixth year of basic education of the “Yaguachi” School in the “Poco a Poco” Campus is about food and its relationship in the development of academic activities of schoolchildren, since the behavior Inappropriate eating conditions the normal development of the activities that the student performs during the academic day, for this reason, the objective of the research is to determine the influence of eating habits on the student's school performance in the educational institution. The methodology that makes up the research process has a qualitative and quantitative approach, where deductive and inductive methods are used, since they allow the segregation of each of the findings found during the study, the type of descriptive research is also applied, because it allows the treatment of all the data reached for the elaboration of general conclusions about the variables under analysis; It is important to state that in order to obtain the information that supports the present research project, the techniques of direct observation and survey were applied, with the objective of determining the student's eating behavior and performance within the classroom, which has allowed establish that eating habits are inadequate, because there is excessive consumption of processed foods, fast foods and artificial juices, that influences their physiological development and performance of daily activities.